(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Term low birth weight neonate represents a heavy burden on healthcare services worldwide due to their higher incidence of morbidity and mortality than term normal weight neonates. Certain maternal factors contribute to delivering term low birth weight neonates. This study was designed to identify the proportion of term low birth weight neonates in a tertiary care hospital and their association with maternal risk factors. Methods: This case-control study was carried out in the Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka over a period of 15 months between April 2017 to June 2018. Term low birth weight (< 2500 gm) neonates delivered in Obstetrics Ward were taken as cases, while the term normal weight neonates taken from the same place were controls. A total of 80 cases and 140 controls who met the eligibility criteria were consecutively included in the study. The maternal factors (that may contribute to the development of term LBW neonates) studied were demographic characteristics, past and current obstetric histories and medical conditions or disease during the last pregnancy. Results: In the present study the proportion of term LBW was 18.6% (80 out 430). Univariate analysis showed that housewives and short statured mothers carry 4(95% CI = 1.5 – 11.0) and 2.3(95% CI = 1.3 – 4.1) times higher risk of having term LBW neonates respectively. Of the obstetric characteristics, primipara and pregnant women with inadequate number of ANCs (< 4 visits) were more prone to have term LBW neonates with risk of having the condition being 2.0(95% CI = 1.1 – 3.7) and 2.2(95% CI = 1.0 – 4.9) times respectively. ANC visit in the 2nd or 3rd trimester had 4.5(95% CI = 1.0 – 4.9) times higher risk of delivering LBW neonates compared to those who made their 1st visit in the 1st trimester (p < 0.001). Mothers who maintained a narrow birth spacing (< 2 years) had a significantly more term LBW babies with likelihood of having the condition being 3-fold (95% CI = 1.2 – 7.9) higher than those who maintained an adequate birth spacing (p = 0.011). Hypertension during pregnancy tend to be significantly associated with term LBW neonates with odds of having the condition being 5.4(95% CI = 2.7 – 10.8) times greater than the normotensive ones (p < 0.001). However, after adjustment by binary logistic regression analysis, inadequate ANC, 1st ANC visit in 2nd trimester onwards, and maternal hypertension during pregnancy emerged as independent predictors of term LBW with Odds of having the condition being 3.61(95% CI = 0.65 – 20.17), 7.56(95% CI = 1.52 – 37.5) and 3.7(95% CI = 1.8 – 7.9) with significance values being p = 0.032, p = 0.013 and p < 0.001 respectively. Conclusion: The study concluded that the mothers with inadequate ANC and 1st ANC visit made in 2nd or last trimester and hypertension carry much higher risk of delivering term LBW neonates compared to their respective counterparts in the same population. Ibrahim Card Med J 2018; 8 (1&2): 23-30